2017
DOI: 10.18585/inabj.v9i2.311
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor Erythroid 2-related Factor 2 (Nrf2) as A Therapeutical Target in Type-2 Diabetes Mellitus: A Review

Abstract: BACKGROUND: Increasing free radicals and oxidative stress due to chronic hyperglycemia in type-2 diabetes mellitus (DM) promotes the activity of endogenic antioxidative genes. Nuclear factor erythroid 2-related factor 2 (Nrf2) expression and activity are important to regulate the production of endogenic antioxidative enzymes.CONTENT: Normally, Nrf2 is bound by protein Kelchlike ECH-associated protein-1 (Keap1) in the cytosol. Stimulation from oxidative stress causes the release of Nrf2 from Keap1. When activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Activation of the NRF2 pathway protects and preserves pancreatic cell mass under hyperglycemia-induced conditions of increased ROS (Baumel-Alterzon et al, 2021). It has been well demonstrated that reducing oxidative stress can be achieved by increasing NRF2 activity when there are elevated ROS (Hendrawati, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the NRF2 pathway protects and preserves pancreatic cell mass under hyperglycemia-induced conditions of increased ROS (Baumel-Alterzon et al, 2021). It has been well demonstrated that reducing oxidative stress can be achieved by increasing NRF2 activity when there are elevated ROS (Hendrawati, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Nrf2 forms a heterodimer and interacts with Keap1 via leucine-zipper groups. (9) Under normal conditions, Nrf2 remains sequestered within the cytoplasm, maintaining low expression levels due to continuous polyubiquitination. However, exposure to various stressors induces Nrf2 expression and prevents ubiquitination.…”
Section: Introductionmentioning
confidence: 99%